Creation of personal branding for lecturers at universitas putra abadi langkat through facebook social media - Okviar Egano Napitupulu, Dea; Syaukani, Arham; Gunawan, Indra; Rafidah, Siti (ProBisnis : Jurnal Manajemen, 2024)
The level of self-recognition of lecturers at Putra Anadi University, Langkat is very low because many lecturers at Putra Abadi University, Langkat do not have a complete portfolio, so they are not able to show data that truly has the capacity and competence of a lecturer, so that it can affect the personal branding of permanent lecturers at the Putra Abadi Langkat Education Foundation, where personal branding that comes from an incomplete portfolio will affect the quality of the lecturers at Putra Abadi University, Langkat. This can be seen from the level of self-recognition (personal branding) of lecturers at UNIPAL on Facebook social media does not appear, because on average UNIPAL lecturers are not active on Facebook social media and do not register academic profiles on Facebook, so the level of UNIPAL lecturers' recognition does not increase and will tend to make the positive image of the lecturer less well-known and result in the level of self-recognition decreasing and having an impact on the decline in the level of UNIPAL's recognition and making the capacity and quality of self regarding the competence of UNIPAL lecturers low which makes UNIPAL unknown to the public and the academic world, so that it affects the level of professionalism of UNIPAL lecturers. The purpose of this study is to find out and analyze the methods used by UNIPAL lecturers to improve personal branding, as well as the impact of personal branding on lecturer professionalism, where the urgency of this study is for lecturers to have integrity and be able to improve their capacity. The research method used is a qualitative descriptive method with the object of research being UNIPAL lecturers who do not show their academic profile and competency profile on Facebook, where data collection techniques are carried out by interview and documentation study. Based on the results of the existing research, it can be explained that there are several strategies that need to be carried out by Lecturers at Putra Abadi University, Langkat in increasing their self-recognition (personal branding) in order to be known as people who have self-capacity and self-quality, namely building the presence of lecturers in the digital world, increasing academic capacity, increasing relationships and networks, and increasing self-quality that the lecturer is an expert in his field. In addition, there is a strong influence of the lecturer's self-recognition (personal branding) in order to improve the professionalism of UNIPAL lecturers, namely increasing the academic reputation of UNIPAL lecturers, increasing opportunities for professional collaboration related to the tri dharma of higher education, becoming a role model for students and other lecturers, and increasing the credibility of lecturers and universities..